Faculty Senate, Minutes, April 26, 2015 - Faculty Senate, Valdosta State University (Valdosta State University Archives and Special Collections, 2015)
Valdosta State University. Faculty Senate, Minutes, April 26, 2015. Michael Noll; James Archibald; Linda Jurczak; Sean Lennon;
1 electronic document. faculty-senate_20150426_minutes.pdf 4 pages. 228803 bytes.
Keywords: Faculty Senate (Valdosta State University); Minutes (Records); Electronic records